An ecological study of NHS funded elective hip arthroplasties in England from 2003/04 to 2012/13. (July 2019) - Sutaria, Shailen; Kirkwood, Graham; Pollock, Allyson M
Objectives: To examine the impact of NHS-funded private provision on NHS provision, access and inequalities. Design: Ecological study using routinely collected NHS inpatient data. Setting: England. Participants: All individuals undergoing an NHS-funded elective hip arthroplasty in England from 2003/2004 to 2012/2013. Main outcome measures: Annual crude and standardised rates of hip arthroplasties per 100, 000 population performed by NHS and private providers between 2004/2005 and 2012/2013. Results: Age standardised rates of hip arthroplasty increased from 116.4 (95% CI 115.4–117.4) to 148.7 (147.6–149.8) per 100, 000 between 2004/2005 and 2012/2013. Provision shifted from NHS providers to private providers from 2007/2008; NHS provision decreased 8.6% and private provision increased 188% between 2007/2008 and 2012/2013. There is evidence of risk selection; private sector hip arthroplasties on NHS patients from the most affluent areas increased 228% from 10.8 (10.2–11.5) to 35.4 (34.3–36.5) per 100, 000 compared to an increase of 186% from 8.8 (8.1–9.4) to 25.2 (24.1–26.4) per 100, 000 among patients from the least affluent areas between 2007/2008 and 2012/2013. There was no statistically significant (p > 0.05) widening in any measure of inequality (absolute, relative difference and slope and relative slope of index inequality) in hip arthroplasty rates between 2004/2005 and 2012/2013. Conclusion: Private provision substituted for NHS provision and did not add to overall provision favouring patients living in the most affluent area. Continuing the trend towards private provision and reducing NHS provision is likely to result in risk selection and widening inequalities in provision of elective hip arthroplasty in England.